Murine alpha-2-macroglobulin increase during inflammatory responses and tumor growth - Isaac, L.; Florido, M. P C; Fecchio, Denise [UNESP]; Singer, L. M. (Springer Nature, 1999)
Objective and Design: To determine the alpha-2-macroglobulin (alpha2M) levels in mice during acute and chronic inflammatory responses. Materials and Methods: Inflammation was induced by one of the following stimuli: carrageenin, zymosan, lipopolysacharide, thioglycollate, bacilli Calmette Guerin, PPD (in pre-immunized and non-immunized animals) and tumor cells. The concentration of alpha2M was determined in plasma or peritoneal liquid by electroimmunoassay. Results: In all the treatments employed, the plasma levels of alpha2M were higher than in untreated animals. This increase varied from 9%, 24 h after injection up a maximum of 66% 72 h post-injection. When compared to animals injected only with saline, the increases were significant 48 h after treatment with either zymosan or LPS, and 72 h after treatment with either thioglycollate or carrageenin. Treatment with BCG triggers an increase in alpha2M levels after 24 h (18.60%) and 48 h (27.90%). Immunized mice presented higher levels of this protein than non-immunized animals after challenge with PPD. The growth of Ehrlich tumor cells in the peritoneal cavity was directly correlated with the local levels of alpha2M which increased 3.5 fold, 10 days after injection. Conclusions: These results strongly indicate that in mice, the concentration of alpha2M can increase during acute and chronic inflammatory reactions with kinetics dependent on the particular kind of inflammatory agent.
Keywords: Acute-phase proteins; Alpha-2-macroglobulin; Cytokine clearance; Protease inhibitor; Tumor; alpha 2 macroglobulin; BCG vaccine; carrageenan; lipopolysaccharide; thioglycolic acid; tuberculin; zymosan; animal experiment; animal model; blood level; cell growth; controlled study; Ehrlich ascites tumor cell; electroimmunoassay; inflammation; male; mouse; nonhuman; peritoneal fluid; tumor growth; Acute-Phase Reaction; alpha-Macroglobulins; Animals; Carcinoma, Ehrlich Tumor; Chronic Disease; Immunoassay; Inflammation; Male; Mice; Mycobacterium bovis; Neoplasm Transplantation; Peritoneal Cavity; Rabbits; Time Factors